2021
DOI: 10.1093/europace/euab116.214
|View full text |Cite
|
Sign up to set email alerts
|

3D mapping versus cardiac computed tomography guided cryoballoon ablation for atrial fibrillation

Abstract: Funding Acknowledgements Type of funding sources: None. Background Cardiac computed tomography (CCT) is an essential tool for an efficient ablation for atrial fibrillation. 3D mapping guided ablation could also deliver sufficient results in the setting of cryoballoon ablation (CBA) with additional advantages regarding total patient radiation exposure, fluoroscopy and procedural time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In case of ablation of atrial fibrillation, recent studies have shown the feasibility and safety of a zero or low fluoroscopy approach 16–19 . In a meta‐analysis of Huang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of ablation of atrial fibrillation, recent studies have shown the feasibility and safety of a zero or low fluoroscopy approach 16–19 . In a meta‐analysis of Huang et al.…”
Section: Discussionmentioning
confidence: 99%
“…In case of ablation of atrial fibrillation, recent studies have shown the feasibility and safety of a zero or low fluoroscopy approach. [16][17][18][19] In a meta-analysis of Huang et al including 2228 procedures, use of 3D mapping in order to achieve zero or low fluoroscopy exposure led to lower fluoroscopy time and DAP. This finding was confirmed in the present study as well, although not reaching statistical significance.…”
Section: Discussionmentioning
confidence: 99%